THE JURISPRUDENTIAL AND LEGAL BASIS FOR AN ELECTRONIC MARRIAGE CONTRACT - Rudainah M. Ridha Majeed (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The marriage contract is one of the most important contracts that can be concluded between two parties, as it is the basis for establishing an important social base in society, which is the family. The marriage contract, like other contracts, is a consensual contract that can only be concluded by mutual consent. It does not require formalism, but rather two wills agree to establish it in the necessary legal form and with the availability of sufficient conditions for its convening. Because contracts, in general, have evolved, like other matters of life, so they have become electronic and are not limited by space or time. Is it possible for the marriage to be electronic and to contract between the two parties remotely? To answer this question, which is the fundamental question of the research, which can be at the end of the answer to establish a new theory that contradicts what is stipulated in the Iraqi Electronic Signature and Electronic Transactions Law No. (78) of 2012. Paragraph 2, M / 3 states that: (It does not apply the provisions of this law are as follows: A- Transactions related to personal status matters and personal items). We will review the jurisprudential and legal evidence necessary to show that a marriage contract can be concluded electronically and for whoever chooses this method to hold it, in preparation for establishing an electronic system to which marriage contracts are subject to in Iraqi courts. In this aspect, we will adopt the analytical approach that depends on presenting the jurisprudential and legal texts and then analyzing them in preparation for reaching the results. Introduction